Voices, land and machines of meaning in Balam Rodrigo’s Central American Book of the Dead - Duarte Somoza, Missael (2026)
This article analyzes Libro centroamericano de los muertos by Balam Rodrigo as a poetic project which intertwines past and present to denounce the structural violence that permeates Central America, particularly through the lens of migration. The text focuses on three analytical axes: voices, land, and the train La Bestia. The first section explores how polyphony is achieved through dramatic monologues that weave together the voices of migrants, historical figures such as Fray Bartolomé de las Casas, and personal references, creating a poetic archive. The second section examines the semantic transformation of Central American territory, which shifts from a symbol of development to a geography of exclusion and forced displacement. Lastly, the train is analyzed as both a technical and semiotic machine, articulating multiple temporalities and reconfiguring its modern symbolism into a device of death. The author engages with theorists such as Félix Guattari and the European avant-gardes to conceptualize machines. Ultimately, the article offers a critical reading of the poem as a poetic intervention in the Central American cultural archive, deconstructing the myth of progress in the region.